Relasi Suami Istri dalam Tinjauan Mubadalah (Telaah atas Hadis Anjuran Istri Mencari Ridho Suami) - Faisal Haitomi (IAIN Syekh Nurjati Cirebon, 2021)
This article discusses the relationship between husband and wife in the family which focuses on the hadith narrated by Ibn Majah through the Musawir al-Himyari route. This hadith is one of the many religious texts that are used as legitimacy for the marginalization of women, especially in the realm of the family. This research borrows the Mubadalah approach offered by Faqihuddin Abdul Kodir as a tool of analysis that emphasizes cooperation and / or alienation between two parties. In simple terms this theory works in three ways, namely: first, linking partial texts (Juz'iyat) with universal principal texts. Second, capturing the main idea or moral ideal of the text being discussed. Third, pass the meaning obtained through the two previous ways to the gender that is not mentioned in the text. From the discussion presented in this paper, the author comes to the conclusion that the hadith about the suggestion of wives to seek and get the approval of their husbands cannot be understood as a party only as emphasized by classical scholars. Partial texts like this when viewed from the point of view of mubadalah, are very contradictory to the teachings of Islamic principles, especially in the family which emphasizes cooperation between husband and wife for the creation of a sakinah family, mawaddah warahmah. therefore it is not only the wife who is encouraged to seek and get the approval of the husband, but also on the other hand, the husband in this case also has the same obligations as that which is borne by the wife.